Melhoria da eficiência de uma linha de produção: uma aplicação do Lean manufacturing em uma indústria metalmecânica - Stella, Cristina (2018)
The search for greater efficiency of resources and lower costs of production are one of the constant searches in most organizations operating in competitive markets. Lean Manufacturing is currently adopted by many companies to achieve these goals, as its philosophy is focused on reducing waste and increasing quality and production efficiency. The present work is a case study carried out in an industry of the metal mechanics sector, aiming to increase the efficiency through the elimination of wastes, allowing improvement of the performance and the organizational competitiveness. After the diagnosis and analysis, the improvement plans were drawn from the sector. Modifications were made in the layout of the sector, measurements in the workstations, application of the 5S, creation of management boards visual, as main results, were evidenced, increase of production capacity, elimination of wastes directly impacting on operational cost and company culture . Having thus an estimated gain of 67% of productive efficiency.